ASSESSMENT OF THE CIRCUMSTANCES AND SEVERITY OFINJURIES IN VICTIMS OF ROAD TRAFFIC ACCIDENTS IN ARCTIC AREA OF ARKHANGELSK REGION - A. V. Baranov; Yu. E. Barachevsky; V. V. Klyuchevsky; S. M. Groshilin (Медицинский вестник Юга России, 2016)
Purpose: assessment of the circumstances and the severity of injuries in victims in the accident , registered in the Arctic zone of the Arkhangelsk region.Materials and methods: we analyzed the medical histories of 327 victims of road traffic accidents in 2012-2014 in Severodvinsk and adjoiningroads of Arkhangelsk region (12-km section of the federal road M-8 «Kholmogory» and a range of regional roads connecting the city with other municipalities).Results: the circumstances of the accidents and severity of victims’ injuries were estimated using a scale of ISS (Injury severity score), the prevalence of injuries of drivers and passengers on the regional roads and injuries of pedestrians — on the roads of Severodvinskwasrevealed.Summary: pedestrians had the most severe injuries on the regional roadsamong other victims, motorcyclists- in urban area. The prevalence of severe concomitant injuries was registered in males.